Energy performance study of a self-cooled membrane-based liquid desiccant dehumidification system - Lin, Lingze (2024)
The pandemic outbreak of COVID-19 has led to a significant impact on global human activity, economic and energy consumption. More researches have focused on novel technologies with higher energy efficiencies to provide comfort indoor environment. Among them, membrane-based liquid desiccant dehumidification system is regarded as an efficient method for air humidity control due to its feasibility without desiccant carry-over problem. Besides, self-cooled liquid desiccant is selected to improve the dehumidification performance. The aim of this study is to develop a novel self-cooled membrane-based liquid desiccant dehumidification system by combining the membrane-based air-liquid contactors with self-cooled liquid desiccant solution. Numerical models for single dehumidifier, regenerator and the complete dehumidification system have been developed based on steady-state heat and mass transfer process using finite difference method. Moreover, experimental works have been conducted to validate the numerical results. It is found that the addition of ethanol into desiccant solution can improve the moisture removal rate (MRR) and dehumidification effectiveness (ε_deh) of the dehumidifier up to 44.7% and 21.8%, respectively. However, the system regeneration ability is reduced compared to pure LiCl aqueous solution. From the complete dehumidification system perspective, the latent cooling output and COP can be increased by 19.57% and 21.98% respectively. The dehumidifier can operate under high effectiveness in different weather conditions, and air flow rate has the most significant influence on its performance. The dehumidification performance benefits from lower inlet solution temperature and higher desiccant concentration. The increase gradient of dehumidifier performance hardly changes when mass flow rate ratio is higher than 1, and effects of the circulate air temperature and flow are negligible. Cooler and drier air can enhance reconcentration ability of the regenerator. The regeneration performance can be improved with higher inlet solution temperature and lower LiCl concentration, and a critical value of mass flow rate ratio m^* = 3 is obtained. For the complete system, the increase of dehumidifier air flow rate will reduce the dehumidification effectiveness but improve the total cooling output and COP, while the effect of regenerator air flow rate is less significant. The performance of the complete dehumidification system can be enhanced by increasing the solution concentration, and the highest COP reaches to 1.2676.